1993
DOI: 10.1182/blood.v81.11.2958.bloodjournal81112958
|View full text |Cite
|
Sign up to set email alerts
|

Increased thrombin generation and activity in patients with systemic lupus erythematosus and anticardiolipin antibodies: evidence for a prothrombotic state [see comments]

Abstract: The objective of this study is to determine whether patients with systemic lupus erythematosus (SLE) and anticardiolipin antibodies (ACA) have biochemical evidence of an ongoing prothrombotic state. Using a cross-sectional analysis of a cohort design in an outpatient SLE clinic setting, 43 consecutive patients with SLE participated. Patients underwent clinical and laboratory evaluations on two separate occasions at least 3 months apart. As part of the clinical evaluation, the following were ascertained: (1) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…After completion of the screening process (►Fig. 1), 18 studies met the criteria for inclusion in the systematic review and meta-analysis: 6 studies investigated both F1 þ 2 and TAT, 3,12-16 7 studies investigated F1 þ 2 only, [17][18][19][20][21][22][23] and 4 investigated TAT only. [24][25][26][27] One of the studies 27 did not report the number of patients positive and negative for aPL, and at the time of submission of this article the authors had not replied to our request for such numbers.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…After completion of the screening process (►Fig. 1), 18 studies met the criteria for inclusion in the systematic review and meta-analysis: 6 studies investigated both F1 þ 2 and TAT, 3,12-16 7 studies investigated F1 þ 2 only, [17][18][19][20][21][22][23] and 4 investigated TAT only. [24][25][26][27] One of the studies 27 did not report the number of patients positive and negative for aPL, and at the time of submission of this article the authors had not replied to our request for such numbers.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
“…Stimulated by this inconsistency, we performed our systematic review to verify how many groups had evaluated a direct relationship between aPL and coagulation activation markers and we then performed a meta-analysis on the available data. With regard to the systematic review, only two articles described aPL mean, 17,25 one aPL range, 21 and one mean LA ratio, 25 whereas the remaining articles reported only the positive or negative aPL status to categorize patient groups; none of the authors attempted a direct correlation of aPL with F1 þ 2 and/or TAT. With regard to the meta-analysis, the majority of the studies included dealt with SLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant association between other clinical findings and fetal wastage was detected. Previous studies have introduced other predictive factors for fetal loss such as preconceptional active lupus nephritis, history of fetal loss, and high antiphosphopholipid antibody titers [30][31][32][33][34][35][36].…”
Section: Renal Involvement and Maternal/infantile Outcomementioning
confidence: 99%
“…3 The association of thrombosis is stronger with persistent than with transient APA. In addition, Ginsberg et al 29 showed that SLE patients with ACA had significantly higher plasma fibrinopeptide A and prothrombin fragments (F1+2) levels than ACA-negative patients. The association between APA and thrombosis extends beyond the setting of SLE to other autoimmune diseases.…”
Section: Clinical Events Associated With Antiphospholipid Antibodies mentioning
confidence: 99%